Sequential induction of NF-kappa B/Rel family proteins during B-cell terminal differentiation. - Liou, H C (1994)
The NF-kappa B/Rel family of at least five transcription factor polypeptides is thought to function both as a developmental regulator in B cells and as a rapid response system in all cells. To examine this notion in more detail, we determined the protein contents of both the inducible and constitutive NF-kappa B/Rel activities in a pre-B-cell line, 70Z/3, and a mature B-cell line, WEHI 231. NF-kappa B p50/p65 is the major inducible nuclear complex after lipopolysaccharide or phorbol myristate acetate treatment of 70Z/3 cells. The constitutive and inducible complexes in WEHI 231 cells are mainly composed of p50 and Rel. The constitutive or induced activities are all sensitive to I kappa B-alpha, but this inhibitor is very short-lived in WEHI 231 cells, suggesting that the balance between synthesis and degradation of I kappa B-alpha determines whether a particular cell lineage has constitutive activity. A patterned expression of the NF-kappa B/Rel activator proteins emerges from an analysis of other B-lineage cell lines and splenic B cells: mainly p50 and p65 in pre-B (and non-B) cells, a predominance of Rel and p50 in mature B cells, and expression of p52 and RelB in plasmacytoma lines. This ordered pattern of regulators may reflect the requirement for expression of different genes during terminal B-cell differentiation because different combinations of NF-kappa B/Rel family members preferentially activate distinct kappa B sites in reporter constructs.